2015
DOI: 10.1111/cbdd.12631
|View full text |Cite
|
Sign up to set email alerts
|

Considerations of Protein Subpockets in Fragment‐Based Drug Design

Abstract: While the fragment-based drug design approach continues to gain importance, gaps in the tools and methods available in the identification and accurate utilization of protein subpockets have limited the scope. The importance of these features of small molecule–protein recognition is highlighted with several examples. A generalized solution for the identification of subpockets and corresponding chemical fragments remains elusive, but there are numerous advancements in methods that can be used in combination to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 156 publications
0
18
0
Order By: Relevance
“…In addition to increasing the throughput of iterative screens, multifragment-binding approaches can enhance second and/or third fragment effects in environments where induced-fit or conformational selection are operative. 23 This can be true when searching for novel fragment pairs demonstrated by the de novo discovery of NLys-NPip-NBal. Previous studies were able to identify the small-molecule T2AA as an inhibitor in cellular systems.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to increasing the throughput of iterative screens, multifragment-binding approaches can enhance second and/or third fragment effects in environments where induced-fit or conformational selection are operative. 23 This can be true when searching for novel fragment pairs demonstrated by the de novo discovery of NLys-NPip-NBal. Previous studies were able to identify the small-molecule T2AA as an inhibitor in cellular systems.…”
Section: Discussionmentioning
confidence: 99%
“…Cavity segmentation into subcavities is crucial in the era of structurebased drug discovery, with medicinal chemists attempting to improve potency and selectivity of their hits by filling protein subpockets. 29,[52][53][54][55] Similar proteins may have binding pockets with different subcavities and dissimilar proteins may have conserved subcavities. Many drug targets exhibit well-defined subpockets geometrically, such as proteases, kinases and GPCRs, which are used extensively in order to develop selective compouds.…”
Section: Enclosure Of Grid Pointsmentioning
confidence: 99%
“…Many drug targets exhibit well-defined subpockets geometrically, such as proteases, kinases and GPCRs, which are used extensively in order to develop selective compouds. 53 In addition, two independent studies concluded that drug-like ligands typically occupy about a third of their binding pockets, filling only some of the subpockets. 56,57 Efforts have been made to try to characterize the chemical fragment preference of certain residues, 58,59 and link the fragment chemical space to binding pocket microenvironments.…”
Section: Enclosure Of Grid Pointsmentioning
confidence: 99%
“…Instead of the weak binding of the compound, fragments are highly efficient ligands and display a high binding affinity per heavy atom. [9,22,23] Furthermore, it is also possible to supplement an existing structure with known affinity by the biochemical target, such as a substrate, or a drug already present in the therapeutic to increase the affinity. Then, the fragments could be modified or linked to yield potent inhibitors.…”
Section: Successful Applicationsmentioning
confidence: 99%
“…Then, the fragments could be modified or linked to yield potent inhibitors. [9,22,23] Furthermore, it is also possible to supplement an existing structure with known affinity by the biochemical target, such as a substrate, or a drug already present in the therapeutic to increase the affinity. [24] From the analysis of the affinity between a series of fragments and the target, it is possible to extrapolate the affinity of compounds formed using these fragments.…”
Section: Successful Applicationsmentioning
confidence: 99%